DISCIPLINE MASTERING LEVEL AND COMPETENCY MASTERING LEVEL: POSSIBILITY TO INTEGRATE THE ESTIMATIONS - Evgeny N. Malyshev; Nikolay V. Vasilyev (Высшее образование в России)
The articleproposes anapproach which enables an integration of two estimations - the assessment of discipline mastering level and the assessment of competency mastering level. Disciplinary examinations, tests, and other control measures need to be fully focused on the identification of student’s level of competence formation. This allows the estimations obtained by students in disciplinary control events to translate in assessing the competence level. The article is an example of a communication matrix between competencies and disciplines, estimations of their mastering level applying to Bachelor programmeof Mechanical Engineering. An important characteristic of the proposed method is the ability to quantify the level of competence. There is a possibility of establishing and monitoring the planned competence level. The technique is universal and is essentially independent of competence content.